Is there an inter-manufacturer difference in generic clopidogrel response?. (3rd October 2022) - Hall, S; Xia, Y; Ahmed, H; Iskhakov, D; Alviar, C; Berger, J; Keller, N; Bangalore, S
Abstract: Background: Differences in platelet aggregation response to generic clopidogrel by manufacturer has not been investigated. Purpose: Compare rates of clopidogrel response among patients receiving medication produced by two different manufacturers after acute coronary syndrome and/or percutaneous coronary intervention. Methods: This quality improvement project included 515 adult patients receiving clopidogrel for acute coronary syndrome or ischemic heart disease and referred for coronary angiography/percutaneous coronary intervention at a large, public hospital. The project was divided into two phases: 1. retrospective collection of baseline data; 2. two 12-week, prospective phases in which all clopidogrel in the hospital was restricted to a single manufacturer at a time. The primary outcome was clopidogrel response measured by platelet function testing defined as ADP response <40% on light transmission aggregometry between two manufacturer groups. Aspirin response defined as arachidonic acid response <20% was also measured. Results: Of 515 total patients included in both phases (mean [SD] age, 64.5 [11.4] years; 351 [68.2%] men; 450 [87.4%] ACS), 52% were found to be clopidogrel responders based on results of platelet function testing (Table 1 – select variables). Among 135 patients in the prospective phase, there was a significantly lower proportion of patients who were clopidogrel responders in the Manufacturer 1 group compared to the Manufacturer 2 group (34.8% vs. 55.1%, p=0.03) (Table 2 – select variables). After adjustment for age, sex, BMI, aspirin response, therapeutic hypothermia, LHC indication, clopidogrel loading dose, time between loading dose and lab measurement, and manufacturer, aspirin response (OR [95% CI]: 0.96 [0.95–0.97], p<0.001) and manufacturer (OR [95% CI]: 2.45 [1.18–5.22], p=0.02) were associated with clopidogrel response. Conclusions: In a large public hospital, we observed that pharmacodynamic response to clopidogrel varied by drug manufacturer. Further investigation and/or regulation is needed to minimize inter-manufacturer variability. Funding Acknowledgement: Type of funding sources: None.